2015
DOI: 10.14778/2752939.2752945
|View full text |Cite
|
Sign up to set email alerts
|

A performance study of big data on small nodes

Abstract: The continuous increase in volume, variety and velocity of Big Data exposes datacenter resource scaling to an energy utilization problem. Traditionally, datacenters employ x86-64 (big) server nodes with power usage of tens to hundreds of Watts. But lately, low-power (small) systems originally developed for mobile devices have seen significant improvements in performance. These improvements could lead to the adoption of such small systems in servers, as announced by major industry players. In this context, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 26 publications
(49 reference statements)
0
34
0
1
Order By: Relevance
“…As stated in previous works [14], ARM-based architectures are not univocally superior to traditional datacenter infrastructures neither in raw data processing nor in standard energy usage. In a first instance this seems to oppose the optimistic findings of Svandeldt-Winter [15], but we must consider the excellent improvements to x86 energy state management in the last few years, which have Figure 7.…”
Section: Discussionmentioning
confidence: 82%
“…As stated in previous works [14], ARM-based architectures are not univocally superior to traditional datacenter infrastructures neither in raw data processing nor in standard energy usage. In a first instance this seems to oppose the optimistic findings of Svandeldt-Winter [15], but we must consider the excellent improvements to x86 energy state management in the last few years, which have Figure 7.…”
Section: Discussionmentioning
confidence: 82%
“…Their performance has improved over time, however, they are not yet as powerful as traditional data center servers. Existing work has studied the use of low power processors for handling data center workloads like web servers [14] and big data [15]. It has been shown that popular Raspberry Pi's are efficient for hosting static web servers while consuming less power than a standard server [14].…”
Section: A Experimental Setup and Profiling Resultsmentioning
confidence: 99%
“…It has been shown that popular Raspberry Pi's are efficient for hosting static web servers while consuming less power than a standard server [14]. ARM processors also offer interesting consumptionperformance ratios for database query processing compared to an Intel Xeon processor [15]. On the other hand, these studies show performance limitations, concluding that these equipments cannot compete with standard servers for more demanding workloads such as dynamic web servers or I/O intensive big data applications.…”
Section: A Experimental Setup and Profiling Resultsmentioning
confidence: 99%
“…The first category is to seek energy proportionality with non-energyproportional servers [53,32,31,27,35]. The second category is to build more energy-efficient architecture based on low-power CPU [38,41,49,33,43,46,29].…”
Section: Related Workmentioning
confidence: 99%
“…Some of these non-traditional server platforms are equipped with low-power processors, such as ARM-based CPU [38,41,49], Intel Atom CPU [33,43,46,29,25] or even embedded CPU [21,50]. In addition to low-power CPU, more energyefficiency can be achieved by exploiting low-power flash storage [25,21] or highly customizable FPGA [40].…”
Section: Related Workmentioning
confidence: 99%